A concept analysis of nurses' commitment to patient care - J.N. Mekwa; L.R. Uys; M.V. Vermaak (AOSIS, 1992)
Commitment to the service of mankind has always been a key concept of professional nursing. However, very little effort seems to have been made to analyse the nature of commitment as a factor in nursing. This article explores the meaning of the concept 'commitment' as revealed by a review of the literature and the responses of a group of registered nurses in unstructured interviews. It goes on to analyse the concept by means of a number of techniques such as an analysis of critical attributes, the construction of model cases and related cases, the identification of antecedents and consequences and of empirical referents. The information gleaned was used to structure a study of the commitment to patient care of a group of professional nurses which will be published in a subsequent article.